Relationship between Characteristics and Nutrient Intake with Anemia among Pregnant Women at Kebon Jeruk Public Health Center, Jakarta - Nadiyah Nadiyah; Elsye Meilinda Sembiring Meliala; Acnes Cristina Simanjuntak; Frisella Perangin-Angin (International Journal of Nursing and Health Services (IJNHS), 2021)
The number of anemia pregnant women in Indonesia increased to 48.9% in 2018. The number of maternal deaths in DKI Jakarta (2018) risen from 53 out of 100,000 live births, with 25% of them due to bleeding and infection. Anemia increases the risk of bleeding and infection. This study aimed to explore the characteristics, nutrient intake among pregnant women, and their relationships with anemia in Public Health Center Kebon Jeruk, West Jakarta. This cross-sectional study was carried out with 60 pregnant women. Two non-consecutive-24 hours dietary recalls assessed energy and protein intake. Micronutrient intakes (iron, folate, vitamins C, B6, B12, E, copper, calcium) were assessed using a semi-quantitative food frequency questioner. Independent t-test or Mann-Whitney and chi-square tests were applied, according to the type of data and interpretation need, to analyze the relationship between characteristics, nutritional intakes, and anemia. The result showed that trimester, mother's education, husband's income, nutritional status, intake of energy, protein, vitamins C, B6, B12, E, folate, iron, copper, and calcium were significantly related to anemia. A well-planned Communication, Information, and Education (IEC) are needed to improve the quality of nutrient intakes and increase adherence to iron tablet consumption